An experimental investigation on natural convection of non-covalently functionalized MWCNTs nanofluids: Effects of aspect ratio and inclination angle. (February 2020) - Samadzadeh, Asma; Zeinali Heris, Saeed; Hashim, Ishak; Mahian, Omid
Abstract: An experimental analysis was conducted to study natural convection heat transfer of water-based nanofluids. Two enclosures with the length × width × height(cm) dimensions of 10 × 10 × 10 and 20 × 10 × 10 and the inclination slopes of 0, 45 and 90° were considered. One of the walls was cooled and the opposite wall was heated. Multi-walled carbon nanotube (MWCNT)/water nanofluids were used as the heat transfer fluid while the MWCNTs were non-covalently functionalized by gum Arabic (GA). The MWCNT-GA/water nanofluids were prepared using 0.005, 0.05 and 0.1 wt% nanoparticles. According to the results, adding MWCNTs to water reduced free convection heat transfer in both enclosures. The effect of increasing MWCNT concentration on Nusselt number was found to be greater than the impact of changing Rayleigh number. Furthermore, free convection heat transfer increased with reducing inclination angle from 90° to 0° at high Rayleigh numbers. It was noticed that changing inclination angle has no considerable influence on Nusselt number at lower Rayleigh numbers. Moreover, free convection heat transfer increased about 8.77% with increasing the aspect ratio from 1 to 2. The highest reduction of Nusselt number was attributed to a system with the aspect ratio, concentration and inclination angle of 1, 0.1 wt% and 90°, respectively.